Correlation for Species Concentration on a Hypersonic Stagnation Point with Mass Injection - Dataset - Ewenz Rocher, M; Hermann, T; McGilvray, M; Gollan, R (University of Oxford, 2022)
This paper presents a correlation to obtain the surface species concentration on a stagnation point with mass injection for hypersonic flow. The correlation can be used to determine surface recombination heat fluxes and oxidation levels for ablatives or actively cooled heat shields in thermochemical equilibrium flow. It explicitly expresses the wall species concentration as a function of freestream conditions, coolant properties, and the stagnation-point geometry, revealing the direct effect of the aforementioned parameters on the desired quantity. The method was compared against the numerically obtained self-similar solution and showed an accuracy of4%. The concentration depends on the boundary-layer edge pressure, temperature, and velocity gradient, as well as the wall temperature and injected mass flux. The molar mass and diffusion coefficient are further needed for scaling if the injected gas differs from the freestream gas.